Pengaruh Permainan Edukasi Voli Fun Game Dalam Pembelajaran PJOK Di Sekolah Dasar - Yanuarius Ricardus Natal; Syrilus Alexandria Pesi; Nikodemus Bate; Robertus Lili Bile (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Abstract This study aims to analyze the effect of the Voli Fun Game educational game-based activity (or simply: educational activity) on learning motivation and basic volleyball skills of elementary school students. The research employed a quasi-experimental design with a pretest–posttest control group design. The research subjects consisted of 30 fifth-grade students who were divided into an experimental group and a control group. The research instruments included a basic volleyball skills test and a learning motivation questionnaire. Data were analyzed using descriptive statistical analysis and a t-test. The results showed that there was a significant difference between the experimental group and the control group (p < 0.05). The Voli Fun Game educational activity proved to be effective in improving students’ learning motivation and basic volleyball skills. It can be concluded that the Voli Fun Game educational activity can be used as an alternative instructional model in Physical Education for elementary schools.